Characterization of in situ synthesized hydroxyapatite/polyetheretherketone composite materials - Rui Ma; Luqian Weng; Xujin Bao; Zhuo Ni; Shenhua Song; Weiquan Cai (2012)
Hydroxyapatite/polyetheretherketone (HA/PEEK) composite materials have potentials for use as loadbearing orthopedic materials due to PEEK outstanding properties, which could overcome the disadvantages of currently used metallic and ceramic materials. In the study HA/PEEK compositematerials were successfully prepared via an in situ process, for the first time, in order to improve the mechanical performance of the existing HA/PEEK composites. The structure of the lab-synthesized materials was characterized by infrared spectroscopy (FTIR), X-ray diffraction (XRD) and scanning electron microscopy (SEM), and the mechanical performance was investigated by a tensile strength test. The results exhibit the strong bonding between hydroxyapatite fillers and PEEK matrix and good mechanical properties of the composites, suggesting that the in situ synthesized HA/PEEK composite materials are promising for orthopedic applications.